Metaphorical Utterances in Taylor Swift’s 2022 NYU Commencement Speech : Tuturan Metaforis dalam Pidato Wisuda Taylor Swift di New York University Tahun 2022 - Siti Alifa Nurhaliza; Sahla Syifa Azkiya; Tatu Siti Rohbiah (Universitas Tidar, 2026)
This study explores the figurative expressions present in the commencement speech delivered by Taylor Swift at New York University in 2022. The study aims to pinpoint the various types of conceptual metaphors and to analyze the connection between literal and figurative meanings by using a cognitive semantic perspective. The goal is to show how metaphors serve not just as persuasive tools but also as cognitive instruments that assist audiences in grasping complex ideas. A qualitative descriptive approach was employed in this research, utilizing the Metaphor Identification Procedure (MIP) proposed by the Pragglejaz Group, together with the Conceptual Metaphor Theory developed by George Lakoff and Mark Johnson. The data for this analysis came from the transcript of Taylor Swift’s speech, from which 20 metaphorical phrases were chosen through purposive sampling. The results indicate that structural metaphors are the most prevalent, constituting 11 phrases (55%), while ontological metaphors account for 9 phrases (45%). Notably, no significant orientational metaphors were found in the address. Additionally, the analysis reveals that the ties between literal and figurative meanings are formed through cross-domain mapping, where tangible experiences clarify abstract ideas such as identity, emotional weight, adaptation, and direction in life. These results suggest that the metaphors used in the speech are crucial for shaping meaning and enhancing audience connection.